Novel Classification System of Rib Fractures Observed in Infants1. Issue 2 (13th February 2013) - Love, Jennifer C.; Derrick, Sharon M.; Wiersema, Jason M.; Pinto, Deborrah C.; Greeley, Christopher; Donaruma‐Kwoh, Marcella; Bista, Bibek
Abstract Rib fractures are considered highly suspicious for nonaccidental injury in the pediatric clinical literature; however, a rib fracture classification system has not been developed. As an aid and impetus for rib fracture research, we developed a concise schema for classifying rib fracture types and fracture location that is applicable to infants. The system defined four fracture types (sternal end, buckle, transverse, and oblique) and four regions of the rib (posterior, posterolateral, anterolateral, and anterior). It was applied to all rib fractures observed during 85 consecutive infant autopsies. Rib fractures were found in 24 (28%) of the cases. A total of 158 rib fractures were identified. The proposed schema was adequate to classify 153 (97%) of the observed fractures. The results indicate that the classification system is sufficiently robust to classify rib fractures typically observed in infants and should be used by researchers investigating infant rib fractures.